Comparison of the Reduction Effect of Sucrose and Table Sugar Concentration on Growth Characteristics of Red Ginger (Zingiber officinale Rocs.) Cultured in Liquid Medium - Hapsari, Betalini Widhi; Ermayanti, Tri Muji; Rantau, Deritha E.; Rudiyanto, Rudiyanto (ANNALES BOGORIENSES, 2011)
The aim of this research was to compare the reduction effect of sucrose or table sugar concentration on growth characteristics of red ginger cultured in MS liquid medium. Shoots of red ginger was cultured on MS liquid medium without addition of plant growth regulators, supplemented with 5, 10, and 20 g/l of sucrose or table sugar for 8 weeks. Resulted plantlets were acclimatized in a greenhouse to investigate their growth and survival rate. Numbers of stomata, chlorophyll concentration as well as cross section of leaves from plantlets grown in vitro were compared to those of transplants grown in the greenhouse. The results showed that the use of table sugar at concentration of 20 g/l gave the best growth of red ginger. Meanwhile, the reduction of table sugar from 20 to 10 g/l reduced growth and survival rate of in vitro shoots as well as that of transplants in the greenhouse. Only few shoots formed roots when they were grown on the medium containing 5 g/l of table sugar, and transplants failed to grow in the greenhouse. It found that the chlorophyll content of in vitro plantlets was lower than those of transplants grown in the glasshouse. However, the number of stomata of the in vitro plantlets was higher than that of transplants grown in the glasshouse. There was no anatomical abnormalities found on the cross section of leaves between in vitro plantlets and transplants grown in the greenhouse. The replacement of sucrose with table sugar may reduce the production cost of plantlets.Keywords: red ginger (Zingiber officinale Rocs.), reduction of sugar, survival rate, chlorophyll, stomata.